Microalgae-mediated green synthesis of silver nanoparticles: a sustainable approach using extracellular polymeric substances from Graesiella emersonii KNUA204 - Do, Jeong-Mi; Hong, Ji Won; Yoon, Ho-Sung (Frontiers in Microbiology, 2025)
Traditional nanoparticle synthesis relies on chemical and physical methods that often involve hazardous reagents, high energy consumption, and environmental toxicity. As a sustainable alternative, biological synthesis utilizes biomolecules in an eco-friendly manner to form nanoparticles. This study explores the green synthesis of silver nanoparticles (AgNPs) using extracellular polymeric substances (EPS) secreted by the microalga Graesiella emersonii KNUA204, highlighting the potential of microalgal biomolecules in nanotechnology. EPS-rich supernatant from G. emersonii enabled AgNP formation under light without the need for biomass pre-processing. The effects of culture age, pH (optimal at 10–11), and tetracycline as a secondary stabilizer were examined. Tetracycline accelerated AgNP formation in dark conditions but could not fully substitute light-induced reduction. The synthesized AgNPs and tetracycline-assisted AgNPs (Tetra-AgNPs) were characterized using UV-visible spectroscopy, EDX, XRD, FTIR, TEM, and Zeta potential measurements, confirming their crystalline, spherical, and moderately stable properties. Biological assays showed strong antibacterial activity at 10 μg mL−1, though Tetra-AgNPs did not outperform AgNPs or tetracycline alone, suggesting structural incorporation of tetracycline. Both AgNPs and Tetra-AgNPs showed similar antioxidant activity. These findings support the potential of G. emersonii KNUA204 for dual biomass utilization, integrating biofuel production with nanomaterial synthesis. Further optimization of EPS composition and biosynthesis conditions could enhance nanoparticle properties for biomedical and environmental applications, reinforcing microalgae as a platform for sustainable nanotechnology.